MO995: Survival Benefits of Kidney Transplantation for Waitlisted Patients in the Contemporary Era. (3rd May 2022) - Chaudhry, Daoud; Peracha, Javeria; Sharif, Adnan
Abstract: BACKGROUND AND AIMS: BACKGROUND. Kidney transplantation is recognised as the treatment of choice for people living with kidney failure who are suitable for surgery. However, with evolving donor-recipient characteristics, survival benefits attributed to kidney transplantation warrants validation in the contemporary era. Therefore, this national cohort study aimed to examine survival of waitlisted hemodialysis-maintained kidney failure patients from the last two decades, comparing those who proceed with transplantation versus those who did not. METHOD: A retrospective cohort study was undertaken of prospectively collected registry data of all waitlisted kidney failure patients receiving hemodialysis in the United Kingdom. From 1 January 2000 until 30 September 2019 inclusive, all patients listed for their first single kidney transplant were included. The primary outcome was mortality, with survival analysis conducted according to the intention-to-treat principle. Time-to-death from listing was modelled using weighted estimation of Cox regression to account for non-proportional hazards. RESULTS: A total of 40 887 waitlisted kidney failure patients formed the study cohort, of whom 31 037 (75.9%) underwent transplantation. Transplant recipients were younger with lower proportion of females, minority ethnics, and diabetes. In a weighted Cox regression model, mortality risk was higher within 30 days of surgery, risk equivalent between 31 and 180 days with survival benefit thereafter. Hazard ratios for mortality within 1 year (HR: 0.575, 95% CI: 0.531–0.623, P< 0.001) and 1–5 years (HR: 0.129, 95% CI: 0.116–0.143, P  < 0.001) of surgery favor transplantation. Survival benefit was retained for every donor type in sub-group analysis, but no survival benefit was observed for patients aged ≥70 within 5 years of transplant surgery. CONCLUSION: In the contemporary era, kidney transplantation remains the superior treatment modality for waitlisted kidney failure patients from a survival perspective but not among older recipients.